Vested Interests in Legal and Judicial Reform - World Bank (Washington, DC, 2017)
This report analyzes the main reasons or interests that have prevented some recent judicial and legal reforms in Honduras and Bolivia from becoming effective. It focuses on the reasons why criminal justice reforms were unable to put an end to the misuse of pre-trial detention. The report also includes a study of some of the reasons that have prevented criminal procedure code reforms from reducing the perception of impunity prevailing in both countries. With respect to the reforms of judicial selection mechanisms, it focuses on the interests that have prevented the public perception of judicial independence from improving in spite of the implementation of those reforms. The report includes an annex to Section 1, consultations with civil society in Honduras. Section 2 discusses civil and commercial justice in Paraguay. Section 3 discusses vested interests in legal and judicial reform projects in Guyana.